E-Commerce Application Design With Web-Based Codeigniter Framework - Zuhri Ramadhan; Fachrid Wadly; Geby Citra Ananda (Yayasan Sinergi Multidimensi Kreatif, 2024)
The development of technology and information that we feel today has a big influence, especially in the world of work. One of them is the use of computers that can facilitate and expedite work. Computers in the business world, both private companies and government agencies, act as hardware that runs software that can be understood by users. In this era of rapid technological development, business people are required to keep up with the times in order to compete with other business people. The solution to buying and selling transactions without meeting directly is done online through website-based e-commerce. One of the web-based e-commerce applications can be designed using the codeigniter framework.